TRPM2: a multifunctional ion channel for calcium signalling - Sumoza-Toledo, Adriana (Blackwell Science Inc, 2011)
The transient potential receptor melastatin-2 (TRPM2) channel has emerged as an important Ca(2+) signalling mechanism in a variety of cells, contributing to cellular functions that include cytokine production, insulin release, cell motility and cell death. Its ability to respond to reactive oxygen species has made TRPM2 a potential therapeutic target for chronic inflammation, neurodegenerative diseases, and oxidative stress-related pathologies. TRPM2 is a non-selective, calcium (Ca(2+))-permeable cation channel of the melastatin-related transient receptor potential (TRPM) ion channel subfamily. It is activated by intracellular adenosine diphosphate ribose (ADPR) through a diphosphoribose hydrolase domain in its C-terminus and regulated through a variety of factors, including synergistic facilitation by [Ca(2+)](i), cyclic ADPR, H(2)O(2), NAADP, and negative feedback regulation by AMP and permeating protons (pH). In addition to its role mediating Ca(2+) influx into the cells, TRPM2 can also function as a lysosomal Ca(2+) release channel, contributing to cell death. The physiological and pathophysiological context of ROS-mediated events makes TRPM2 a promising target for the development of therapeutic tools of inflammatory and degenerative diseases.